Предмет: Алгебра,
автор: Ostag
Помогите решить уравнение 9x+9-x³-x²=0
Ответы
Автор ответа:
1
9x+9-x³-x²=0
9(х+1) - х²(х+1) = 0
(х+1)(9-x²) = 0
(x+1)(3-x)(3+x) = 0
x+1 = 0 или 3-х=0 или 3+х=0
х = -1 х=3 х=-3
Ответ: х=-3, х=-1, х=3
9(х+1) - х²(х+1) = 0
(х+1)(9-x²) = 0
(x+1)(3-x)(3+x) = 0
x+1 = 0 или 3-х=0 или 3+х=0
х = -1 х=3 х=-3
Ответ: х=-3, х=-1, х=3
Автор ответа:
1
9x + 9 - x³ - x² = 0
9(x + 1) - x² (x + 1) = 0
(x + 1)(9 - x²) = 0
(x + 1)(3 - x)(3 + x) = 0
или x + 1 = 0 ⇒ x₁ = - 1
или 3 - x = 0 ⇒ x₂ = 3
или 3 + x = 0 ⇒ x₃ = - 3
Ответ : - 3 ; - 1 ; 3
9(x + 1) - x² (x + 1) = 0
(x + 1)(9 - x²) = 0
(x + 1)(3 - x)(3 + x) = 0
или x + 1 = 0 ⇒ x₁ = - 1
или 3 - x = 0 ⇒ x₂ = 3
или 3 + x = 0 ⇒ x₃ = - 3
Ответ : - 3 ; - 1 ; 3
Похожие вопросы
Предмет: Английский язык,
автор: hiznakmarina09011982
Предмет: Математика,
автор: Аноним
Предмет: Музыка,
автор: polino4ka090908
Предмет: Физика,
автор: Jimin111
Предмет: География,
автор: Bukovskatус